Sharia Hospital As An Added Value: Sharia Hospital Competitive Excellence Strategy Based On Positioning - Nugroho, Arif Julianto Sri; Almasitoh, Ummu Hany; Tasari, Tasari; Supratikno, Supratikno; Christanti, Paramita Lea; Santoso, Agus (Journal of Applied Management Research, 2024)
This research aims to determine the excellent position of each sharia hospital in Klaten Regency so that it can determine the right marketing strategy to satisfy and increase public interest in trusting the quality of services provided by sharia hospitals. This research was carried out with a quantitative approach through Multivariate multidimensional scaling statistical tests. The novelty of the research combines the concept of competitive excellence, quality performance of sharia health service institutions through position mapping using a multidimensional scaling model. The population in the study were all people who had used sharia hospital services in Klaten. The sample of respondents was taken using a purposive sampling technique as many as 120 adult respondents. Attributes in the questionnaire include Sharia facilities, paramedical services, medical expertise, medical atmosphere and facilities, administrative services. In the final stage of the research, a map of the position of each sharia hospital was formed so as to create the competitiveness of each excellent sharia hospital in Klaten Regency to welcome the era of achieving SDGs goals and achieving optimal sharia economic growth in the health sector in 2045